Performance in a complex coincident timing task with disacceleration of visual stimulus in individuals of different ages - Pinheiro, João de Paula; Corrêa, Umberto Cesar (Brazilian journal of physical education and sport, 2005)
The aim of this study was to investigate the performance in a complex task of coincident timing with deceleration of visual stimulus in individuals of different ages. Participated in the study 60 individuals distributed in four experimental groups: child (n =15), adolescent (n =15), adult (n =15), and elderly (n =15). The instrument used was an apparatus of coincident timing in a complex task. The task consisted of touching five response keys sequentially in conjunction with a visual stimulus. Each individual executed 15 trials. The results revealed that the adolescents presented smaller absolute error, followed by adults, children, and elderly. In the variable error, the adolescents presented smaller error, follow by adults, elderly, and children. For the constant error, the children presented a trend towards a delay in the response, while adolescents, adults and elderly a tendency to advance it.